1999
DOI: 10.1139/f98-200
|View full text |Cite
|
Sign up to set email alerts
|

The regime concept and natural trends in the production of Pacific salmon

Abstract: Large fluctuations in the trends of Pacific salmon production in this century have been linked to trends in climate in the Pacific that are in turn associated with climate trends throughout the Northern Hemisphere. The close correspondence in the persistence of climate trends and the synchrony of the changes is evidence that a common event may cause the regime shifts. The trends or regimes can be characterized by stable means in physical data series or multiyear periods of linked recruitment patterns in fish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(131 citation statements)
references
References 65 publications
2
116
0
1
Order By: Relevance
“…The PDO was demonstrated to affect ocean productivity and eddy activities at the high-and mid-latitudes 1958-1967 (purple line), 1968-1977 (brown line), 1978-1987 (green line), 1988-1997 (blue line) and 1998-2009 (red line), and the IPCC A2 scenario in sea surface temperatures (SSTs) in 2050 and 2075 (grey lines) in Taiwan Strait in winter of the North Pacific (Tian et al 2008;Tzeng et al 2012a). Numerous studies have provided compelling evidence connecting the PDO and variations in the Pacific marine ecosystems and fisheries, such as sardine populations off the coasts of Japan, California, Chile, and Peru (Yasuda et al, 1999) and Pacific salmon catches in eastern Asia and western North America (Beamish et al, 1999). The results of our study showed that catch rates of grey mullet have increased after 1972 with the regime shift to positive PDO and showed similar fluctuations with 4 to 8-year cycles from .…”
Section: Effects Of Climate Change On Grey Mullet Catches and Fishingmentioning
confidence: 99%
“…The PDO was demonstrated to affect ocean productivity and eddy activities at the high-and mid-latitudes 1958-1967 (purple line), 1968-1977 (brown line), 1978-1987 (green line), 1988-1997 (blue line) and 1998-2009 (red line), and the IPCC A2 scenario in sea surface temperatures (SSTs) in 2050 and 2075 (grey lines) in Taiwan Strait in winter of the North Pacific (Tian et al 2008;Tzeng et al 2012a). Numerous studies have provided compelling evidence connecting the PDO and variations in the Pacific marine ecosystems and fisheries, such as sardine populations off the coasts of Japan, California, Chile, and Peru (Yasuda et al, 1999) and Pacific salmon catches in eastern Asia and western North America (Beamish et al, 1999). The results of our study showed that catch rates of grey mullet have increased after 1972 with the regime shift to positive PDO and showed similar fluctuations with 4 to 8-year cycles from .…”
Section: Effects Of Climate Change On Grey Mullet Catches and Fishingmentioning
confidence: 99%
“…Climate prediction models and our understanding of the mechanisms linking salmon and climate response in the North Pacific Ocean continue to improve as we learn more about the biological response of Pacific salmon to environmental variation and as our long-term data records on ocean condition and salmon production increase (Beamish et al, 1999). The major climate influence on salmon production is thought to operate in a bottom-up fashion through physical influences on primary and secondary production (Brodeur and Ware, 1992;Roemmich and McGowan, 1995).…”
Section: Global Change Anthropomorphic Effects and Nonlinearity In mentioning
confidence: 99%
“…Climate change can directly affect physical environmental conditions critical to Pacific salmon in both freshwater (Schindler, 2001) and marine habitats (Beamish et al, 1999). The magnitude and timing of these changes can produce broadscale and local shifts in the distribution and abundance of salmon (Mantua et al, 1997).…”
Section: Global Change Anthropomorphic Effects and Nonlinearity In mentioning
confidence: 99%
“…Two of these so-called ''regime shifts'' have been identified in the past 30 years. One occurred in the winter of 1976-1977, in which the Pacific Decadal Oscillation (PDO) underwent a strong transition and the Arctic Oscillation (AO) underwent a moderate transition; the second shift occurred in the winter of 1988-1989 when the PDO switched to a more or less neutral state, and the AO underwent a strong, persistent change (Ebbesmeyer et al, 1991;Hare and Francis, 1995;Sugimoto and Tadokoro, 1998;Beamish et al, 1999;Brodeur et al, 1999a;Hare and Mantua, 2000). Both the AO and the PDO are related to variability in the climate of the southeastern Bering Sea (Overland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%